Reducing the Number of Elements in Phase-Only Reconfigurable Arrays Generating Sum and Difference Patterns - Morabito, Andrea Francesco; Rocca, Paolo (IEEE antennas and wireless propagation letters, 2015)
A new strategy for the synthesis of one-dimensional reconfigurable sparse arrays generating sum and difference power patterns is presented. In order to reduce the weight and complexity of the beam forming network, the design procedure provides solutions in which only one set of amplitude coefficients is required and just a π phase shift is needed for half array to switch between the two radiation modes. The synthesis is cast as the solution of a Linear Programming problem plus a local optimization procedure where the sparseness of the array layout is achieved by properly exploiting the principles of Compressive Sensing. Examples concerning the design of monopulse antennas show relevant savings of array elements with respect to conventional architectures.